2007
DOI: 10.1128/jb.00714-07
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin Reductase Is Essential for Thiol/Disulfide Redox Control and Oxidative Stress Survival of the Anaerobe Bacteroides fragilis

Abstract: Results of this study showed that the anaerobic, opportunistic pathogen Bacteroides fragilis lacks the glutathione/glutaredoxin redox system and possesses an extensive number of putative thioredoxin (Trx) orthologs. Analysis of the genome sequence revealed six Trx orthologs and an absence of genes required for synthesis of glutathione and glutaredoxins. In addition, it was shown that the thioredoxin reductase (TrxB)/Trx system is the major or sole redox system for thiol/disulfide cellular homeostasis in this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 59 publications
(75 reference statements)
5
60
1
Order By: Relevance
“…The thioredoxin system (thioredoxin, thioredoxin reductase and NADPH) is a disulfide-reducing system present in a variety of bacteria and has been demonstrated to protect cells against oxidative stress. Our results are also consistent with other reports that demonstrate induction of these genes upon exposure to oxygen in P. gingivalis (Diaz et al, 2006;Meuric et al, 2008) as well as in the related bacterium B. fragilis (Rocha et al, 2007).…”
Section: Oxygen Detoxification Genes Are Induced In Aerobic Conditionssupporting
confidence: 83%
“…The thioredoxin system (thioredoxin, thioredoxin reductase and NADPH) is a disulfide-reducing system present in a variety of bacteria and has been demonstrated to protect cells against oxidative stress. Our results are also consistent with other reports that demonstrate induction of these genes upon exposure to oxygen in P. gingivalis (Diaz et al, 2006;Meuric et al, 2008) as well as in the related bacterium B. fragilis (Rocha et al, 2007).…”
Section: Oxygen Detoxification Genes Are Induced In Aerobic Conditionssupporting
confidence: 83%
“…Mutant strains were constructed by allelic exchange (see Fig. S1 in the supplemental material) as described previously using the suicide vector pFD516 and the PCR primers described in Table S1 in the supplemental material (53). For the construction of mutant BER63, 400 bp from the central portion of the ftnA gene was deleted and replaced with a 2.2-kb tetQ gene fragment.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly as in many non-pathogenic organisms' genomes, also in pathogens have been identified a number of Trx and TrxR. For example, Trx system is a major thiol-disulfide redox system in gram-negative, opportunistic pathogen B. fragilis (Rocha et al 2007) and contains six genes encoding homologues of Trx and one gene for TrxR (Reott et al 2009). Recently studies revealed that not all Trx proteins are still active and providing an active protection.…”
Section: Thioredoxin System Of Selected Pathogens As a Therapeutic Tamentioning
confidence: 99%